Capitalismo extrativista na América Latina e as contradições da mineração em grande escala no Brasil - Gonçalves, Ricardo Junior de Assis Fernandes (Universidade de São Paulo - Programa de Pós-graduação em Integração da América Latina, 2017)
In the first decade of the 21st century, the increase in the price of mineral commodities such as iron ore, copper, gold and aluminum, strengthened the expansion of new frontiers of mineral extraction in Latin America. Thus, the objective of this research is to understand the effects of mining on the economy and in territories impacted by mega projects in Latin American countries. For this, in a second moment the centrality of the investigation prioritized the Brazilian reality. The model of extractive mineral extraction based on the great projects strengthens strategies of control of the territories and accumulation by spoliation. The scale of production and consumption, methods and extractive rhythms, as well as the use and waste of the own minerals, water and energy, illustrate the unsustainability and contradictions of mining in Brazil and in Latin America.